CARACTERIZAÇÃO DO PERFIL SENSORIAL E NUTRICIONAL DE CHOCOLATES COMERCIAIS ATRAVÉS DA ESPECTROSCOPIA DE INFRAVERMELHO E CALIBRAÇÃO MULTIVARIADA - Costa, Ludmila Pinheiro (2011)
This work investigates the application of infrared spectroscopy, assisted by multivariate data analysis techniques, to model nutritional and sensorial parameters from chocolates with different cocoa amount. After constructing their sensory profile, eighteen commercial chocolate samples (milk, bitter and bitter-sweet) were analyzed by near and mid infrared, using Diffuse Reflectance Infrared Fourier Transform (DRIFT) and Attenuated Total Reflectance (ATR). The database structure was inspected by Principal Component Analysis (PCA), while the sensory properties and the nutritional parameters were modeled by Partial Least Squares Regression (PLSR). Despite of the modeling of sensory parameters did not presented satisfactory results; it was possible to construct good models for buy intention, fat, proteins and carbohydrates content.